Pengaruh Edukasi Teknik Relaksasi Napas Dalam Berbasis Audiovisual Terhadap Skala Nyeri Pasien Pasca Bedah Di Ruang Perawatan Bedah Di Salah Satu Rumah Sakit Swasta Di Yogyakarta - Suryaningsih, Yustina; Rina Setyani, Fransisca Anjar; Widianti, Christina Ririn (STIKes Panti Rapih, 2022)
Background: surgery can cause acute pain, this is caused because during surgery there is tissue damage that triggers cytokine discharge. Approximately 80% of patients undergoing surgery experience acute postoperative pain. 40% of patients experience moderate and severe pain during the first 24 hours after surgery. Planning related to pain management needs to be well prepared before surgery. One of the efforts that can be done to prevent the impact of postoperative pain is by educating pre-surgery by using pain management videos. By using audio visual media, the patient will more easily understand and perform pain reduction techniques. Purpose: to determine the effect of preoperative pain management on the postoperative patient pain scale. The research was conducted at one of the private hospitals in Yogyakarta on February 11-March 07, 2021. Method: Research design using pre experiment posttest only design, Population in this study as many as 41 respondents, sample selection is done with purposive sampling technique. The samples in this study were 30 divided into two groups, namely 15 respondents of the intervention group who were given education on deep breath relaxation techniques using video and 15 respondents of the control group. Result: data analysis conducted with Mann-Whitney test, obtained the result of p value 0.123 ( p value > 0.05), meaning there is no difference in the pain scale of the intervention group respondents and the control group. Conclusion: nurses should motivate and do mentoring when the patient applies the deep breath relaxation techniques that have been taught